Catalog of the spiders of Tunisia (Arachnida: Araneae) - Kmira, Ghassen; Nasri-Ammar, Karima; Petillon, Julien; Bosmans, Robert (Zootaxa, 2025)
A comprehensive catalog of all species of the order Araneae from Tunisia is presented, based on a compilation of data from all published sources up to the present. The catalog documents 423 species belonging to 224 genera and 45 families, including 28 endemic species. Six species are considered as nomina dubia in the World Spider Catalog (2025), and therefore removed from the list together with 18 others, with explanations provided for their exclusion. A total of 1377 records is obtained, and each species is documented with all its localities cited in the literature. The taxonomic composition, number and distribution of records in the country are analyzed. The most speciose families are Gnaphosidae (52 species), Theridiidae (51 species), Linyphiidae (45 species), Salticidae (42 species) and Lycosidae (29 species); together (219 species), they represent more than half of the species currently known to the country. The distribution of records is considerably uneven both taxonomically and geographically. A striking 187 species, representing 44.1% of the Tunisian spider fauna, are recorded from only a single locality. By contrast, only 79 species, representing 18.6% of Tunisian spiders, are recorded from more than five localities. Some localities, especially major cities, have been intensively sampled, while vast regions, like the desert, remain underexplored. In addition to cataloging, this study reviews the history of araneology in Tunisia and highlights the necessity of expanding research beyond taxonomic and faunistic studies. The present status and future perspectives of araneology in Tunisia are discussed, with recommendations for advancing araneological research in the country. This work represents the most detailed and comprehensive documentation of spiders in Tunisia so far, paving the way for future research and conservation of these arachnids in the country.